PENGARUH PENERAPAN LKS BERNUANSA KETERAMPILAN BERPIKIR KRITIS DALAM PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SMA N 2 PADANG - Nina Risti Ananda; Hufri Hufri; Nurhayati Nurhayati (Universitas Negeri Padang, 2016)
Thinking critically is needed in solving problem or finding solution. The background of this research is still lack students worksheet that can develop the ability of the student’s critical thinking. Scientific approach can help the students to build the knowledge through this scientific method. The solution to solve this problem is use a worksheet that can practice the ability of a student’s thinking. The purpose of this research is to observe the effect of application worksheet nuanced critical thinking skill in scientific approach to the learning outcomes of Physics students grade X at SMAN 2 Padang. The population of this research is all students Xth grade at SMAN 2 Padang in academic year 2015/2016. Sampling by purposive sampling technique. Data of this research includes student learning outcomes in the cognitive, affective and psychomotor. Research instrument are written test, evaluation sheets and sheet performance attitude. Based on the analysis data obtained on average student learning outcomes of experiments class on the cognitive, affective and psychomotor is 80,49; 78.71; and 79.29. The result of this research that there is a significant influence of the application worksheet nuanced critical thinking skill in scientific approach to the learning outcomes of Physics students grade X at SMAN 2 Padang